High genetic diversity including potential new subtypes of hepatitis C virus genotype 6 in Lao People's Democratic Republic - Hubschen J.M. (2014)
Sera from 105 anti-HCV-positive first-time blood donors collected in 2004, 2005 and 2008 in different provinces in Laos were investigated by PCR. Forty-five samples were positive for HCV (42.86%); two belonged to subtype 1b (2/45, 4.4%) and all others to genotype 6 (43/45, 95.6%), including subtypes 6b, 6h, 6k, 6l, 6n and 6q. Three groups of sequences were not clearly attributable to any genotype 6 subtype, two of which may be regarded as candidates for new subtypes of genotype 6. Two samples were mixed infected with different subtypes or clusters of genotype 6 viruses. © 2011 The Authors. Clinical Microbiology and Infection © 2011 European Society of Clinical Microbiology and Infectious Diseases.